Potentials and challenges of phosphorus recovery as vivianite from wastewater: A review. (July 2019) - Wu, Yang; Luo, Jingyang; Zhang, Qin; Aleem, Muhammad; Fang, Fang; Xue, Zhaoxia; Cao, Jiashun
Abstract: Due to the shortage of phosphorus resources and the limitations of existing phosphorus recovery methods, phosphorus recovery in the form of vivianite has attracted considerable attention with its natural ubiquity, easy accessibility and foreseeable economic value. This review systematically summarizes the chemistry of vivianite, including the characteristics, formation process and influencing factors of the material. Additionally, the potential of phosphorus recovery as vivianite from wastewater has also been comprehensively examined from the prospects of economic value and engineering feasibility. In general, this method is theoretically and practically feasible, and brings some extra benefits in WWTPs. However, the insufficient understanding on vivianite recovery in wastewater/sludge decelerate the development and exploration of such advanced approach. Further researches and cross-field supports would facilitate the improvement of this technique in the future. Graphical abstract: Image 1061 Highlights: Vivianite formation is a complex process and is influenced by various factors. P recovery as vivianite contributes to the sustainable use of P with high value. The potential to recover vivianite from wastewater in WWTPs is great. More research is required for the efficient vivianite recovery from wastewater.